Radiographical and Anatomical Assessment of Mandibular Mental Foramen Variations for a Sample of Yemeni Patients Undergoing Dental Implant Placement - Aldilami, Abdulwahab; Al-Maqtari, Osama; AL-Jawfi, Khaled; Al-Najjar, Latifa; AL-Hudaid, Ali; Hwaiti, Hisham; Shamala, Anas (Radiance Research Academy, 2023)
Aim: To assess the prevalence, diameter and location of mental foramen MF, and Accessory mental foramen AMF, by cone beam computed tomography (CBCT) for a Sample of Yemeni Patients. Methodology: The study was an analytical retrospective cross-sectional study conducted on 420 CBCT images of mandibles referred from general practitioners, surgery departments and surgeons for implant demands. The data collection took from April 2018 to July 2018. The sample size was divided according to gender, age, side, and dental condition. The images were analyzed and the measurements were done using the tools given in the software (Ez3D plus with Ez3D-I software). Results: MF was found in all patients (51.4% males and 48.6% females). The means of the MF diameter, MF-H, MF-V, MF-M1, MF-M2, AMF-HMD and AMF-VMD were 2.60 mm, 3.74 mm, 3.08 mm, 7.61 mm, 10.99 mm, 1.88 mm and 1.63 mm, respectively. Most of the cases were located under the apex of the 2nd premolar was found in only 4 (1%) of all cases. Conclusion: The most prevalent location of the MF was under the long axis of the 2nd premolar. The round shape of the MF was more prevalent than the oval shape.